Gastric Mucosa-associated Lymphoid Tissue Lymphoma: An Important Differential Diagnosis for a Rapidly Growing Gastric Subepithelial Tumor - A Case Report and Literature Review - Nah Ihm Kim; Dong Hyun Kim; Hyun Soo Kim; Seon-Young Park; Hyun A Cho; Ho-Goon Kim (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Gastric mucosa-associated lymphoid tissue (MALT) lymphoma is a low-grade lymphoma with a long median survival time because of its low proliferation rate. A 75-year-old man was referred to the hospital for hematemesis. Upper endoscopy revealed a 30-mm subepithelial tumor (SET). Abdominal CT and EUS revealed a homogeneously hypoechoic lesion arising from the second layer of the stomach, without distant metastasis. Laparoscopic wedge resection was performed. On microscopic examination, the tumor showed diffuse aggregation of small lymphoid cells with abnormal architecture. Neoplastic cells showed positive reactivity for CD20 and prominent lymphoepithelial lesions were observed. The urease breath test was also conducted, with a negative result. Our final diagnosis was Helicobacter pylori-negative MALT lymphoma (Ann Arbor classification IE2), which is a rapidly growing SET pattern. This case highlights the importance of including gastric MALT lymphoma as a differential diagnosis for rapidly growing gastric SETs.